Pengaruh Dimensi Corporate entrepreneurship dan Performa Firma: Sebuah Studi Kualitatif - Kirana, Indah Pramesthi; Purnomo, Margo; Purbasari, Ratih (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
Corporate entrepreneurship is an entrepreneurial activity done at a well-established firm level, to help the firm adjust to the dynamic market by pushing the innovation ability and venturing for business in the company. Despite being interestingly important, not many companies realize how important corporate entrepreneurial mindset is for the sustainability of the business. This research aims to prove how Corporate entrepreneurship and its dimensions can shape the firm’s reputation and growth for a long time. This research was done by the systematic literature review (SLR) method from well-reputed journal articles based on the SCOPUS database to prove the effectiveness of Corporate entrepreneurship dimensions over firm performance. From this research, we found that Corporate entrepreneurship will affect the firm’s performance, especially financial performance. The dimensions created a mindset of proactiveness that will lead to the wish for further research that focused on the Corporate entrepreneurship dimensions with more varied sectors and wider countries on the scope.